Pengenalan Amicus Curiae sebagai Instrumen Hukum Formal untuk Meningkatkan Integritas Peradilan - Johannes Edison Haholongan (Ikatan Hakim Indonesia (IKAHI), 2024)
The submission of Amicus Curiae’s brief in the court has created a new paradigm that emerges and develops within the society itself. Such practice, which had already been developed in many judiciaries in other countries, could in fact be utilized by the Indonesian judiciary as a means to improve its integrity, namely by capturing the development of legal values and sense of justice within the society at large. Nevertheless, currently there have been no formal legal grounds to regulate the Amicus Curiae. Consequently, such condition has created confusion within those who presented themselves to become Amicus Curiae in the court. This paper intends to examine the possibility of formal recognition of Amicus Curiae as a full-fledged legal instrument in the court. Moreover, this paper also investigates various appropriate legal basis to accommodate the formal application of the Amicus Curiae in the court. Finally, this paper will endeavor to argue that the application of the Amicus Curiae as a formal legal instrument could be used by the Indonesian judiciary to enhance its integrity within the society itself.